A Systematic Literature Review of Innovation Capabilities and Technology Adoption for Sustainable School Performance - Isnawati Isnawati; Supardi Supardi (Dinasti Information and Technology, 2026)
Sustainable school performance has become a strategic issue in the field of education, driven by technological advancements, demands for improved educational quality, and the need for adaptive school management. Innovation capabilities and technology adoption are viewed as key factors that can enhance organizational effectiveness, the quality of educational services, and the sustainability of school performance. This study aims to identify, analyze, and synthesize the results of previous research on the relationship between innovation capabilities, technology adoption, and sustainable school performance through a Systematic Literature Review (SLR) approach. The research method followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, which include the stages of identification, screening, eligibility assessment, and article inclusion. Data were obtained from scientific articles indexed in Scopus and published between 2016 and 2026 in accordance with the established inclusion criteria. The results of the study indicate that innovation capabilities contribute to enhancing schools’ ability to adapt to change, drive continuous improvement, and strengthen the organization’s learning culture. On the other hand, technology adoption has been shown to improve administrative efficiency, the quality of the learning process, data-driven decision-making, and collaboration among stakeholders. A literature review also indicates that the integration of innovation capabilities and technology adoption has the potential to lead to more sustainable school performance. Nevertheless, empirical research examining the simultaneous relationship between these two variables and sustainable school performance remains relatively limited, particularly in the context of developing countries. Therefore, this study provides a comprehensive synthesis of existing research, identifies research gaps, and proposes a future research agenda as a foundation for developing conceptual models and conducting empirical research in the field of educational management.